Modern drying technology - Tsotsas, Evangelos; Mujumdar, Arun S. (Weinheim : Wiley-VCH, 2007)
This five-volume handbook provides a comprehensive overview of all important aspects of modern drying technology, including only advanced results.
V. 1. Computational tools at different scales -- v. 2. Experimental techniques -- v. 3. Product quality and formulation -- v. 4. energy savings -- v. 5. Process intensification.
Includes indexes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Drying; Drying; Electronic books